STRATEGI PENGEMBANGAN KREATIVITAS SISWA MELALUI MEDIA LOOSE PARTS - Novitasari, Nurul; Nilna Zulfiana, Hilmi; Masruroh, Farhatin (Atthufulah : Jurnal Pendidikan Anak Usia Dini, 2024)
The purpose of this thesis research is to find out the use of Loose Parts media in developing students' creativity in the Al Khoiriyah Muslimat NU Bangilan Tuban Playgroup. The research used is qualitative research. The research location was in the Al Khoiriyah Muslimat NU Playgroup, Bangilan District, Tuban Regency. Data collection techniques were carried out using observation techniques, interviews and documentation. The data sources for this study amounted to 2 people, namely: school principals, class teachers in Group B. Data analysis used 3 stages, namely data reduction, data display and drawing conclusions. Based on the process of data collection and data analysis, researchers can conclude several things. Loose art is a learning media that consists of loose materials and how to use them can be used alone or in combination with other materials. After using loose parts media students began to be active in various learning activities, students began to show their interests and talents, could think critically and were able to experiment with the materials provided, students' creativity also increased compared to previous students and there were fifty percent of students who creativity increased after using loose parts media.